3
$\begingroup$

Find $\frac{dy}{dx}$ if $y=\sin^{-1}\frac{2x}{1+x^2}$

The solution is given as $\frac{2}{1+x^2}$. But is it a complete solution ?

My Attempt

$$ 2\tan^{-1}x=\begin{cases}\sin^{-1}\frac{2x}{1+x^2},\quad |x|\leq 1\\ \pi-\sin^{-1}\frac{2x}{1+x^2},\quad |x|>1 \;\&\; x>0\\ -\pi-\sin^{-1}\frac{2x}{1+x^2},\quad |x|>1 \;\&\;x>0\\ \end{cases}\\ \sin^{-1}\frac{2x}{1+x^2}=\begin{cases}2\tan^{-1}x,\quad |x|\leq 1\\ \pi-2\tan^{-1}x,\quad |x|>1 \;\&\; x>0\\ -\pi-2\tan^{-1}x,\quad |x|>1 \;\&\;x>0\\ \end{cases}\\ $$ Thus, $$ \frac{dy}{dx}=\frac{d}{dx}\bigg[\sin^{-1}\frac{2x}{1+x^2}\bigg]=\begin{cases} \frac{d}{dx}[2\tan^{-1}x]=\frac{2}{1+x^2},\quad |x|\leq 1\\ \frac{d}{dx}[\pm\pi-2\tan^{-1}x]=\frac{-2}{1+x^2},|x|>1 \end{cases} $$ Is it correct ?

$\endgroup$
2
$\begingroup$

Note that

  • $(\sin^{-1}x)'=\frac{1}{\sqrt{1-x^2}}$

then apply chain rule $f(g(x))'=f'(g(x))g'(x)=\frac{\frac{2(1+x^2)-4x^2}{(1+x^2)^2}}{\sqrt{1-{\left(\frac{2x}{1+x^2}\right)}^2}}=\frac{2(1-x^2)}{(1+x^2)|1-x^2|}$

$\endgroup$
  • $\begingroup$ could u comment on my attempt ?. why am i getting two case ? $\endgroup$ – ss1729 Mar 23 '18 at 17:09
  • $\begingroup$ @ss1729 so you are looking for a direct proof? $\endgroup$ – user Mar 23 '18 at 17:10
  • $\begingroup$ @ss1729 the final result seems to be correct, but why use the $tan^{-1}$ for the derivation? $\endgroup$ – user Mar 23 '18 at 17:15
  • $\begingroup$ Why do toy thunk that you should be getting one case? $\endgroup$ – Michael McGovern Mar 23 '18 at 17:16
  • 1
    $\begingroup$ @ss1729 yes by chain rule I've derived exactly your result $\endgroup$ – user Mar 23 '18 at 17:36
0
$\begingroup$

Hint Your answer seems correct to me even I don't really understand the need of tan function

$$y=\sin^{-1}\frac{2x}{1+x^2} \implies \sin y=\frac{2x}{1+x^2}$$ Differentiate $$y'\cos(y)=\frac {-2(x^2-1)}{(x^2+1)^2}$$ use the fact that $$\sin^2(y)+\cos^2(y)=1$$

$\endgroup$
  • $\begingroup$ hw do u proceed it without substituting for x ? $\endgroup$ – ss1729 Mar 23 '18 at 17:27
  • $\begingroup$ differentiate both sides and note that $(\sin(y))'=\cos(y)y'$ $\endgroup$ – Satyendra Mar 23 '18 at 17:29
  • $\begingroup$ what about RHS ?. $\cos yy'=\frac{(1+x^2).2-2x.2x}{(1+x^2)^2}=\frac{2+4x^2+2x^4-4x^2}{(1+x^2)^2}=\frac{2(1+x^4)}{(1+x^2)^2}$ Now what ? $\endgroup$ – ss1729 Mar 23 '18 at 17:33
  • $\begingroup$ you have the value of $\sin(y)$ use $cos^2(y)+sin^2(y)=1$ to get rid of the $cos(y)$ $\endgroup$ – Satyendra Mar 23 '18 at 17:35
  • $\begingroup$ This answer is good when you dont know the derivative of arcsin function .... $\endgroup$ – Satyendra Mar 23 '18 at 19:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.